Legal Dilemma of Using Diplomas as Collateral in Employment Relationships - Rifo Rinaldi; Hono Sejati; Tri Susilowati (Journal of World Science, 2024)
The concern in Indonesia is that explicit regulations addressing this issue still need to be improved. This study aims to analyze the legal dilemmas surrounding diploma retention, identify weaknesses in current regulations, and propose solutions to protect employee rights. Using a normative juridical approach, this research employs statutory and conceptual methodologies. Data were collected through document analysis of legal statutes, employment agreements, and relevant legal literature. The findings indicate that ambiguity in regulatory frameworks concerning legal sanctions leads to repeated violations and construction failures.  The findings reveal that diploma retention as collateral needs a solid legal foundation, creating an imbalance of power that disadvantages employees. The study highlights the novelty of examining diplomas as collateral within the broader principles of collateral law, offering new perspectives on their inapplicability as valid collateral objects. By proposing clear regulatory frameworks and alternative approaches, such as proportional penalties, the study contributes to safeguarding workers’ rights while addressing employers' concerns. These findings aim to promote fairness and legal certainty in employment practices.